Práticas alimentares e abastecimento na Manaus oitocentista (1848 – 1863) - PINHO, Robert Alves (2024)
The objective of this dissertation is to analyze food in the city of Manaus during the second half of the 19th century, highlighting the historical possibilities presented by food and the relationships that can be perceived in its production process. Food practices are understood as consumption, forms of consumption and production of food, as well as the relationships present in the manufacture of the genres presented in this work. Supply is the second factor analyzed, using a historiography that sees, in the supply of the cities of the Empire, the development of local markets, still little studied, and the circulation of goods in the provinces furthest from the imperial centers, are also analyzed supply crises, and the formation of the city's supply network, and development of a political elite linked to supply, which exploited human and non-human resources.